Notes on the Hodge conjecture for Fermat varieties. (16th July 2021) - Clingher, Adrian; da Silva, Genival
Abstract: We review a combinatoric approach to the Hodge conjecture for Fermat varieties and announce new cases where the conjecture is true. We show the Hodge conjecture for Fermat fourfolds X_m^4 of degree m ≤ 100 coprime to 6, and also prove the conjecture for X_21^n and X_27^n , for all n.